Conception d’un site web pour la commercialisation des produits agricoles - HADJIDJ, Souha Talia; CHOULI, Lamis (My University, 2024)
The creation of an e-commerce website dedicated to the commercialization of agricultural products in Algeria aims to transform the agricultural and commercial landscape of the country. The main goal of this project is to facilitate transactions between producers and consumers by providing them with a modern and efficient digital platform. By eliminating intermediaries, producers can increase their visibility and reach a broader market, while consumers benefit from direct access to fresh and high-quality products. This initiative promises to invigorate the Algerian agricultural sector, stimulate innovation, and create economic opportunities for local producers.